Pengalaman ibu nifas terhadap budaya dalam perawatan masa nifas - Endriyani, Agustin (Jurnal Kebidanan, 2020)
The influence of culture to the status of public health could not be ignored, health is an integral part of the culture. Ethnographic research results in health the year 2012 at 12 ethnics in Indonesia show the maternal and child health issues related to health culture is very concern. The purpose of this research is to know the experience of maternal childbirth to culture in the care period of parturition. This research was qualitative research with case studies. In-depth interview data collection methods (in-depth interview). Snowball sampling techniques. Participants in this research were the mother of the parturition is the working relic of clinics Paste. The number of participants that is used in this study is as much as 7 participants. The results of this research obtained 3 themes, namely, the knowledge of the participants towards parturition period care, Influence the culture of the community, treatments against the time of parturition, and family support in the treatment period of parturition.